2021
DOI: 10.2459/jcm.0000000000001237
|View full text |Cite
|
Sign up to set email alerts
|

Proprotein convertase subtilisin/kexin type 9 inhibitors treatment in dyslipidemic patients: a real world prescription

Abstract: Aim Dyslipidemia is recognized as one of the major risk factors for cardiovascular diseases. This retrospective observational study was aimed to assess the effect of proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors in dyslipidemic patients with a lipid profile not well controlled by maximally tolerated statin therapy or intolerant to these lipid-lowering drugs. We enrolled 151 patients, of whom, 119 were taking evolocumab and 32 alirocumab.Results Total cholesterol significantly decreased progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…We have perused with interest the study of Derosa et al regarding the hypolipidemic effect of proprotein convertase subtilisin/kexin type 9 inhibitors (PCSK9i) in an Italian cohort of patients suffering either from hypercholesterolemia or mixed hyperlipidemia. 1 This study adds further evidence to the growing body of literature providing real-world data about the long-term lipid-lowering impact of PCSK9i prescription. In particular, the authors demonstrated that PCSK9i are well tolerated and can significantly ameliorate patients' lipidemic profile as their 4-year prescription was associated with a progressive decrease in patients' total cholesterol (TC) and lowdensity lipoprotein cholesterol (LDL-C) levels.…”
Section: To the Editormentioning
confidence: 53%
See 1 more Smart Citation
“…We have perused with interest the study of Derosa et al regarding the hypolipidemic effect of proprotein convertase subtilisin/kexin type 9 inhibitors (PCSK9i) in an Italian cohort of patients suffering either from hypercholesterolemia or mixed hyperlipidemia. 1 This study adds further evidence to the growing body of literature providing real-world data about the long-term lipid-lowering impact of PCSK9i prescription. In particular, the authors demonstrated that PCSK9i are well tolerated and can significantly ameliorate patients' lipidemic profile as their 4-year prescription was associated with a progressive decrease in patients' total cholesterol (TC) and lowdensity lipoprotein cholesterol (LDL-C) levels.…”
Section: To the Editormentioning
confidence: 53%
“…We have perused with interest the study of Derosa et al regarding the hypolipidemic effect of proprotein convertase subtilisin/kexin type 9 inhibitors (PCSK9i) in an Italian cohort of patients suffering either from hypercholesterolemia or mixed hyperlipidemia 1 . This study adds further evidence to the growing body of literature providing real-world data about the long-term lipid-lowering impact of PCSK9i prescription.…”
mentioning
confidence: 81%
“…Other studies of LDL lowering and side effects involve relatively small numbers of patients (eg, <300). 7 , 8 , 9 , 10 , 16 , 20 , 28 Furthermore, we compared PCSK9-I monotherapy versus PCSK9-I combination therapy with a statin and/or ezetimibe, and we found good adherence among all treatment groups and greater LDL lowering with PCSK9-I combination therapy. These findings have implications for the optimal use of PCSK9-Is in VHA and other health care systems.…”
Section: Discussionmentioning
confidence: 87%
“…While several real-world studies have assessed the side effects and effectiveness (eg, LDL lowering, CV events) of PCSK9-Is, 7 , 8 , 9 , 10 all involved small numbers of patients. Furthermore, while there are multiple studies on the patterns of use, cost, accessibility, adherence, discontinuation, and overall place in therapy of PCSK9-Is in the treatment of hyperlipidemia, 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 these were conducted in populations outside of the VHA. VHA is the largest integrated health care system in the United States and provides access to needed medications with nominal, or no, copayment.…”
Section: Introductionmentioning
confidence: 99%